The role of particle radiotherapy in the treatment of skull base tumors - Iannalfi, Alberto; Riva, Giulia; Ciccone, Lucia; Orlandi, Ester (Frontiers in Oncology, 2023)
Skull base is an anatomically and functionally critical area surrounded by vital structures such as the brainstem, the spinal cord, blood vessels, and cranial nerves. Due to this complexity, management of skull base tumors requires a multidisciplinary approach involving a team of specialists such as neurosurgeons, otorhinolaryngologists, radiation oncologists, endocrinologists and medical oncologists. In case of pediatric patients, the cancer management should be performed by a team of pediatric-traineed specialists. Radiation therapy may be used alone or in combination with surgery to treat skull base tumors. There are two main types of radiation therapy: photon therapy and particle therapy. Particle radiotherapy uses charged particles (protons or carbon ions), that due to their peculiar physical properties, permits to precisely target the tumor with minimal healthy tissue exposure. These characteristics allow to minimize the potential long-term effects of radiation exposure in terms of neurocognitive impairments, preserving quality of life, and radio-induced cancers’ risk. For these reasons in children, adolescents and young adults, proton therapy should be an elective option when available. In radioresistant tumors such as chordomas and sarcoma and previously irradiated recurrent tumors, particle therapy permits to deliver high biologically effective doses with low or however acceptable toxicity. Carbon ion therapy has peculiar and favorable radiobiological characteristics in order to overcome radioresistance features. In low grade tumors, proton therapy should be considered in challenging cases for tumor volume and involvement of critical neural structures. However, particle radiotherapy is still relatively new and more research is needed to fully understand its effects. Additionally, the availability of particle therapy is limited as it requires specialized equipment and expertise. The purpose of this manuscript is to review the available literature regarding the role of particle radiotherapy in skull base tumors treatment.